Anxiogenic Potential of Experimental Sleep Fragmentation Is Duration-Dependent and Mediated via Oxidative Stress State - Grubač, Željko; Šutulović, Nikola; Šuvakov, Sonja; Jerotić, Djurdja; Puškaš, Nela; Macut, Djuro; Rašić-Marković, Aleksandra; Simić, Tatjana; Stanojlović, Olivera; Hrnčić, Dragan (Oxidative medicine and cellular longevity, 2021)
Sleep architecture alterations, among which sleep fragmentation is highly prevalent, represent risk factors for a variety of diseases, ranging from cardiovascular to brain disorders, including anxiety. What mediates anxiety occurrence upon sleep fragmentation is still a matter of debate. We hypothesized that the sleep fragmentation effects on anxiety are dependent on its duration and mediated by increased oxidative stress and alterations in the number of parvalbumin (PV+) interneurons in the hippocampus. Sleep was fragmented in rats by the treadmill method during a period of 14 days (SF group). Rats with undisturbed sleep in the treadmill (TC group) and those receiving equal amounts of treadmill belt motion (EC group) served as controls. To assess anxiety, we subjected rats to the open field, elevated plus maze, and light-dark tests on the 0, 7th, and 14th day. Upon the last test, brain structures were sampled for oxidative stress assessment and PV+ interneuron immunohistochemistry. The results of ethological tests of anxiety-linked behavior suggested duration-dependent anxiogenic potential of sleep fragmentation. Rats’ anxiety-linked behavior upon sleep fragmentation significantly correlated with oxidative stress. The rats with fragmented sleep (SF) showed significantly higher oxidative stress in the hippocampus, thalamus, and cortex, compared to controls (TC and EC), while the antioxidant enzymes’ activity was significantly decreased. No significant differences were observed in hippocampal PV+ interneurons among these groups. Our results showed that duration of sleep fragmentation is a significant determinant of anxiety-linked behavior, and these effects are mediated through oxidative distress in the brain. Herein, it is revealed that the sleep fragmentation-oxidative stress-anxiety axis contributes to our better understanding of pathophysiological processes, occurring due to disrupted sleep patterns.